2020
DOI: 10.1111/jfbc.13230
|View full text |Cite
|
Sign up to set email alerts
|

Esculetin and idebenone ameliorate galactose‐induced cataract in a rat model

Abstract: Cataract is the principal cause of blindness. The enzyme, aldose reductase (AR) is a key player in polyol pathway. Buildup of polyols and oxidative stress are the main causes of cataractogenesis. This study investigated the cytoprotective properties of esculetin and idebenone in galactose‐induced cataract. Rats were partitioned into four groups each of ten rats. Control group was fed with normal diet; group 2 rats were fed with galactose diet (50%); groups 3, 4 rats were fed with galactose diet concurrently wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
1
6
1
Order By: Relevance
“…In contrast to elamipretide and #37, #77 did not show a significant antioxidant effect, which suggests that the protection by #77 appears to involve mechanisms(s) distinct to the other compounds. Idebenone is widely portrayed as being a potent antioxidant [13] but, in the present study, there is no statistically significant antioxidant effect, which is in stark contrast to a previous report, where idebenone significantly reduced markers of oxidative damage in a rat model of cataract formation [39]. This effect was dependent on the route of administration and dose and, while the cataract study used oral idebenone (100 mg/kg), the present study used 10 mg/ml in eyedrops.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to elamipretide and #37, #77 did not show a significant antioxidant effect, which suggests that the protection by #77 appears to involve mechanisms(s) distinct to the other compounds. Idebenone is widely portrayed as being a potent antioxidant [13] but, in the present study, there is no statistically significant antioxidant effect, which is in stark contrast to a previous report, where idebenone significantly reduced markers of oxidative damage in a rat model of cataract formation [39]. This effect was dependent on the route of administration and dose and, while the cataract study used oral idebenone (100 mg/kg), the present study used 10 mg/ml in eyedrops.…”
Section: Discussioncontrasting
confidence: 99%
“…That is in line with Gerhardt et al, 40 who found that IDE inhibited the activation of pro-apoptotic factors in mice. Sadik and her coworkers 41 also supported our results as they reported that IDE ameliorated galactose-induced cataracts in rats through its antioxidant and antiapoptotic properties.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, several in vitro and in vivo studies suggest that idebenone appears to do exactly that. In a model of galactose-induced cataract formation idebenone reduced oxidative damage by increasing total endogenous tissue antioxidant capacity [ 56 ]. This increased antioxidant capacity by idebenone is likely the consequence of an increased expression of a range of endogenous antioxidants such as superoxide dismutase (SOD), catalase, NAD(P)H quinone oxidoreductase 1 (NQO1), glutathione (GSH), and glutathione peroxidase (GPx) [ 37 , 45 , 48 , 49 , 57 ], while also downregulating the superoxide-producing enzyme NOX2 [ 58 ].…”
Section: Is Idebenone a Direct Antioxidant?mentioning
confidence: 99%